2021
DOI: 10.1371/journal.pone.0246548
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in COVID-19 exposures and outcomes in the South: A preliminary analysis of South Carolina

Abstract: As the COVID-19 pandemic moved beyond the initial heavily impacted and urbanized Northeast region of the United States, hotspots of cases in other urban areas ensued across the country in early 2020. In South Carolina, the spatial and temporal patterns were different, initially concentrating in small towns within metro counties, then diffusing to centralized urban areas and rural areas. When mitigation restrictions were relaxed, hotspots reappeared in the major cities. This paper examines the county-scale spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 30 publications
11
98
1
1
Order By: Relevance
“…There were higher numbers of mitigation measures in urban areas, which also contained lower rates of standardized cases and fatalities. Our study confirms previous research investigated over a smaller geographic area that found increased standardized cases and fatalities in rural US counties [13], but contradicts a nationwide study executed earlier in the pandemic finding higher mortality rates in urban counties [30].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…There were higher numbers of mitigation measures in urban areas, which also contained lower rates of standardized cases and fatalities. Our study confirms previous research investigated over a smaller geographic area that found increased standardized cases and fatalities in rural US counties [13], but contradicts a nationwide study executed earlier in the pandemic finding higher mortality rates in urban counties [30].…”
Section: Discussionsupporting
confidence: 78%
“…Urban-rural disparities explored in earlier research found increased mortality rates [30] and higher prevalence rates of COVID-19 infection in urban counties [12]. Another study found higher standardized cases and fatalities in rural counties in just one US state [13], while others found severe negative impacts of the pandemic on rural unemployment and economic wellbeing [10]. Not only do rural residents have higher positive COVD-19 testing rates [26] and fewer hospitalization resources available for affected patients [31,32], but locational disparities exist in testing access and pandemic messaging in rural locations [33].…”
Section: Socioeconomic and Spatial Disparities Of The Covid-19 Pandemicmentioning
confidence: 84%
See 2 more Smart Citations
“…Finally, we examine the impact of geography on willingness to click on ads for CovidDefense. In contrast to the existing body of literature around urban-rural differences in COVID-19 behavior, which finds that rural residents are less concerned about COVID-19 and less likely to adopt pro-social COVID-19 behaviors [27,28,29,30], we find that Louisiana residents in rural communities are significantly more likely to click on any of the proposed ads (O.R. = 1.15; p < 0.001; Appendix Table 6).…”
Section: Resultscontrasting
confidence: 99%